Deformation twinning and grain partitioning in a hexagonal close-packed magnesium alloy. Issue 1 (December 2018) - Arul Kumar, M.; Clausen, B.; Capolungo, L.; McCabe, R.; Liu, W.; Tischler, J.; Tomé, C.
Abstract Pervasive deformation twinning in magnesium greatly affects its strength and formability. The local stress fields associated with twinning play a key role on deformation behavior and fracture but are extremely difficult to characterize experimentally. In this study, we perform synchrotron experiments with differential-aperture X-ray microscopy to measure the 3D stress fields in the vicinity of a twin with a spatial resolution of 0.5 micrometer. The measured local stress field aids to identify the sequence of events involved with twinning. We find that the selected grain deforms elastically before twinning, and the twin formation splits the grain into two non-interacting domains. Under further straining one domain of the grain continued to deform elastically, whereas the other domain deforms plastically by prismatic slip. This heterogeneous deformation behavior may be mediated by the surrounding medium and it is likely to lead to asymmetric twin growth. Magnesium deforms via twins that form in a grain then expand both forward and laterally, causing local stresses that have yet to be measured. Here, the authors measure the full strain and stress tensors around a twin in a bulk polycrystal and show that the twinning grain deforms heterogeneously.